A REVIEW OF INNOVATIVE WORK BEHAVIOR AND INNOVATIVE CULTURE TOWARDS COMPANY PERFORMANCE - Noor Shakina binti Rabul Jalil; Nor Adriana Sofia binti Nornasaruddin; Nor Shuhada binti Saharunizam; Nur Azarina binti Ismail; Siti Nuraisyah binti Abdul Hamid; Aini Qamariah binti Mohd Yusof (International Journal of Accounting, Finance and Business, 2022)
Innovative Work Behavior is a motivation for employees who have high confidence in areas related to the tendency to be innovative in their work behavior in order to develop a successful company. Great innovation necessitates questioning assumptions, focusing on human problems rather than answers, experimenting and collaborating, changing gears and sprinting when necessary, and, most all, embracing positive ambiguity. However, a firm's innovative performance is influenced not just by internal resources, but also by knowledge and skills created outside the organization in collaboration with others. A key factor of performance innovation is the innovation of approach to creating value for customers to remain competitive and have a strategy. This review study is intended to identify the importance of innovative work behavior towards innovative performance and innovative culture. Innovation is also carried in a much contextual literature and has major themes on aspects of usefulness, novelty, creativity. As an action for seek, develop, and implement ideas to solve and help the company achieve the goal of finding a new idea and provide support to the company to support the idea. Innovation research lacks a profound empirical study to date which analyzes the relationship between organizational culture and innovative performance on the firm level.